Hasrat Ekonomi Politisi dan Penurunan Kualitas Demokrasi Indonesia Jelang Pemilu 2019 - Johanis Putratama Kamuri (Societas Dei: Jurnal Agama dan Masyarakat, 2019)
ABSTRACT: This article rests on the thesis that economic interest is the implicit end of Indonesian political agents. Economic interest, the implicit end, is the main driving force that cause the deterioration of the quality of Indonesian democracy. Various phenomena that cause the deterioration of the quality of Indonesian democracy will be understood and explained through the political strategies of Niccolo Machiavelli as a conceptual framework. Furthermore, the ideal political perspective from Bernhard Sutor which is sustained by Marx’s idea of basic and superstructure will be used to find the implicit end which moves political agents and influences existing political phenomena. This article concludes with a number of thoughts that remind and prepare Indonesian society, especially the readers, to seriously consider their political choices in April 2019, in order to improve the quality of Indonesian democracy. KEYWORDS: The implicit end, Indonesian democrasy, economic interests, Indonesian politicians, Indonesian political situation, MachiavelliÂ Â ABSTRAK: Â  Artikel ini bertumpu pada tesis bahwa hasrat ekonomi adalah tujuanÂ  implisit agen politik di Indonesia. Hasrat ekonomi yang menjadi tujuan implisit adalah kekuatan utama yang menyebabkan penurunan kualitas demokrasi di Indonesia. Pemikiran Niccolo Machiavelli merupakan bingkai konseptual untuk memahami dan menjelaskan sejumlah fenomena politik yang mempengaruhi penurunan kualitas demokrasi di Indonesia. Selanjutnya perspektif politik ideal dari Bernhard Sutor yang ditopang oleh konsep basis dan superstruktur dari Marx akan digunakan untuk menegaskan tujuan implisit, visi/tujuan politik, yang menggerakkan politisi dan melatarbelakangi fenomena politik tersebut. Artikel ini diakhiri dengan sejumlah pemikiran yang mengingatkan dan mempersiapkan masyarakat Indonesia, khususnya pembaca, untuk mempertimbangkan pilihan politiknya pada April 2019 secara serius, demi peningkatan kualitas demokrasi di Indonesia. KATA-KATA KUNCI: Tujuan implisit, demokrasi Indonesia, hasrat ekonomi, politisi Indonesia, situasi politik Indonesia, Machiavelli